2012
DOI: 10.1007/s00234-012-1111-z
|View full text |Cite
|
Sign up to set email alerts
|

Imaging findings in seven cases of congenital infantile myofibromatosis with cerebral, spinal, or head and neck involvement

Abstract: In a newborn presenting with intraparenchymal brain lesions, epidural spinal masses, and/or vertebra plana or lytic lesions of the calvarium and spine, infantile myofibromatosis should be considered as a possible differential diagnosis. The presence of subcutaneous or muscular nodules facilitates the diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Radiological examinations can be helpful in assessing the extent of the myo broma/myo bromatosis and its progression and prognosis. However, the plain radiography, computed tomography and magnetic resonance imaging (MRI) ndings of myo broma are mostly case reports and small series [11,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], and some imaging ndings in our study have rarely or never been reported. Our study aimed to describe the multidetector computed tomography (MDCT) and magnetic resonance imaging (MRI) ndings of the myo broma and to correlate them with pathologic features, in order to improve the diagnostic accuracy of preoperative radiological examinations.…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…Radiological examinations can be helpful in assessing the extent of the myo broma/myo bromatosis and its progression and prognosis. However, the plain radiography, computed tomography and magnetic resonance imaging (MRI) ndings of myo broma are mostly case reports and small series [11,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], and some imaging ndings in our study have rarely or never been reported. Our study aimed to describe the multidetector computed tomography (MDCT) and magnetic resonance imaging (MRI) ndings of the myo broma and to correlate them with pathologic features, in order to improve the diagnostic accuracy of preoperative radiological examinations.…”
mentioning
confidence: 78%
“…Myo bromas could occur at any bone, the cranio-orbito-facial bones were most often involved with a solitary lesion, while, the other bone lesions were frequently observed with the multicentric type (17%-77%) [2,7,[15][16][17][18]. On plain radiography and CT, most skeletal lesions demonstrated well-de ned, expansile, osteolytic, with or without a partial or poorly developed sclerotic rim which more commonly observed when the lesions start to heal [14,18,19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The solitary form of IM usually occurs in the skin, subcutaneous tissues, muscles and the skull, with good prognosis (3,16–19). By contrast, the multicentric form of IM widely invades subcutaneous muscles, bones and viscera (1,19,20). Both solitary and multicentric forms of IM are associated with poor prognosis if they affect viscera, particularly the heart, the lungs and gastrointestinal tracts (9,13,18).…”
Section: Discussionmentioning
confidence: 99%